Fatty acid composition of fl owers of Crepis foetida subsp. rhoeadifolia from Turkey - Cengiz Sarikurkcu, Abdurrahman Aktumsek, Olcay Ceylan, Gokhan Zengin (Journal of Medicinal Herbs and Ethnomedicine, 2015)
This study aims to describe the fatty acid composition of flowers of Crepis foetida subsp. rhoeadifolia. In order to define qualitative and quantitative profile, fatty acids were derived to their methyl esters, and then these were analyzed by gas chromatography - flame ionization detector. 20 fatty acids were determined in the oil. Palmitic (C 16:0), myristic (C 14:0), and linoleic acids (18:2 Ï‰6) were found to be major fatty acids. Total saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids (PUFA) were 62.67%, 17.54%, and 19.79%, respectively. Also, total essential fatty acids (EFA) were determined ad 14.48%. Therefore, the oil can be considered as a new source of PUFA, especially EFA.